Efficacy and safety of steroid in the prevention of esophageal stricture after endoscopic submucosal dissection: A network meta‐analysis. Issue 6 (15th January 2019) - Yang, Jiahui; Wang, Xin; Li, Yarui; Lu, Guifang; Lu, Xinlan; Guo, Dan; Wang, Wancong; Liu, Chuan; Xiao, Ye; Han, Nini; He, Shuixiang
Abstract: Background and Aim: Even though endoscopic submucosal dissection is an important endoscopic resection technique for gastrointestinal neoplasms, there are chances that postoperative esophageal stricture might take place as a side effect. Steroid applications were reported to be effective for the prevention of stricture formation. Therefore, this study aims to evaluate the efficacy and safety of different steroid applications. Methods: Eligible studies published on PubMed, the Cochrane Library, Embase, Web of Science, and Chinese Biomedical Literature Database before August 2018 were reviewed. The preventions were divided as placebo/no treatment, long‐term oral steroid (LOS), median‐term oral steroid, short‐term oral steroid, single‐dose steroid injection, multiple‐dose steroid injection, topical superficial steroid, steroid injection combined with oral steroid, and preemptive endoscopic balloon dilatation. The primary outcomes were postoperative esophageal stricture rate and endoscopic balloon dilatation sessions required. Complications were also analyzed. Results: A total of 19 studies were included. The network meta‐results illustrated that compared with the placebo, all kinds of steroid interventions were associated with lower rates of postoperative esophageal stenosis and less number of endoscopic balloon dilatation sessions. Moreover, combined therapy was no better than single regimen therapy. No significant differences between various steroid applications in the incidence of complications were spotted during this study. Based on the results of the network and clustered ranking, LOS might be the superior prevention for postoperative stricture with satisfying efficacy. Conclusion: The present study showed that LOS appears to be the optimal prevention method for postoperative stricture formation.